Diabetic retinopathy: hyperglycaemia, oxidative stress and beyond - Hammes, Hans-Peter (Diabetologia, 2018)
Diabetic retinopathy remains a relevant clinical problem. In parallel with diagnostic and therapeutic improvements, the role of glycaemia and reactive metabolites causing cell stress and biochemical abnormalities as treatment targets needs continuous re-evaluation. Furthermore, the basic mechanisms of physiological angiogenesis, remodelling and pruning give important clues about the origins of vasoregression during the very early stages of diabetic retinopathy and can be modelled in animals. This review summarises evidence supporting a role for the neurovascular unit—composed of neuronal, glial and vascular cells—as a responder to the biochemical changes imposed by reactive metabolites and high glucose. Normoglycaemic animal models developing retinal degeneration, provide valuable information about common pathways downstream of progressive neuronal damage that induce vasoregression, as in diabetic models. These models can serve to assess novel treatments addressing the entire neurovascular unit for the benefit of early diabetic retinopathy.